新加坡华语电影研究1945年至1965年 = A study of Singapore Chinese Films (1945-1965) - 李静欣 Li, Jingxin (2009)
在1920年代，新加坡就已开始有电影制片业。二战结束后到新加坡独立之前，许多制片厂与制片公司在新加坡崛起，摄制了各种类型以及各种语言的影片。这些影片虽以马来语片居多，但也包括数部华语电影。本论文探讨的将是1945年至1965年的新加坡华语故事片。首先，本文会先对此课题中的重要概念“新加坡”、“华语”和“新加坡电影” 作出界定，再从电影的放映与发行、电影制作、资金提供、电影取景四方面对新加坡电影业作出概述。接着，由于目前关于1945年至1965年新加坡华语电影的资料纪录稀少，本文将把焦点放在这时期的十二部电影，通过对各方面搜集的材料之整理，以个案讨论的方式，为这时期的新加坡华语电影建构一个更完整的面貌，同时提出一些发现。再者本文亦以此为基础，结合当时社会上关于此课题的讨论，探讨新加坡华语电影在这时期先后出现的四个特征：中国民族主义的认同、本土意识方面的发展、本土文化的重视、以及种族意识的转变，最后进一步分析这些特征的由来、意义、所形成的发展趋势等等。Singapore ventured into film production as early as the 1920s. After the Second World War till Singapore’s independence, several film studios and film production companies emerged on the island. A variety of films in different genres and languages were made. Although this consisted of mostly Malay several Chinese films were also produced. This thesisaims to discuss the Chinese films produced in Singapore from 1945 to 1965. First, this thesis will start by defining some key concepts in this topic such as “Singapore”, ”Mandarin” and “Singapore films”, and provide an overview of Singapore’s film industry from two main aspects: film screening and distribution, as well as film production. As little is known of Singapore Chinese films produced during the period, a thorough consolidation of related materials from various sources had been executed. This consolidation would be presented as separate case studies of twelve films produced during this period,providing a historical construction of the Chinese film production scene then. Next, using this as a basis, and taking into consideration of the respective social contexts, the analysis would focus on four main characteristics of Singapore Chinese Films during this period, namely an identification with Chinese nationalism, development of local consciousness, emphasis on local culture and the transformation in racial consciousness. In addition, the analysis would also discuss the origins, significance and the trends formed by these four characteristics.